2022
DOI: 10.1088/1742-6596/2278/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Change Detection in Hyperspectral Images using Principal Components Space Data Clustering

Abstract: Change detection of hyperspectral images is a very important subject in the field of remote sensing application. Due to the large number of bands and the high correlation between adjacent bands in the hyperspectral image cube, information redundancy is a big problem, which increases the computational complexity and brings negative factor to detection performance. To address this problem, the principal component analysis (PCA) has been widely used for dimension reduction. It has the capability of projecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These eigenvectors are the principal components that capture the maximum variance in the data. The original data is projected onto the selected k principal components to obtain the reduced-dimensional representation [59]. For the i-th data point, the reduced representation i z is calculated as Eq.…”
Section: Principal Component Analysis (Pca) and Canonical Correlation...mentioning
confidence: 99%
“…These eigenvectors are the principal components that capture the maximum variance in the data. The original data is projected onto the selected k principal components to obtain the reduced-dimensional representation [59]. For the i-th data point, the reduced representation i z is calculated as Eq.…”
Section: Principal Component Analysis (Pca) and Canonical Correlation...mentioning
confidence: 99%
“…In the previous literature, various change detection techniques were developed and improved to enhance the utilization of hyperspectral imagery, such as convolutional sparse analysis, temporal spectral unmixing, 41 recurrent 3D fully convolutional networks, 42 convolutional long short-term memory, 42 modified U-Net model, 43 principal component analysis, and spectral correlation angle. 44 But the processing of hyperspectral bands with such advanced change detection models may be difficult due to the presence of a large number of spectral bands, which may limit its applicability in various applications. Moreover, the existence of radiometric/atmospheric errors in the hyperspectral dataset may make it difficult for change detection models to identify subtle changes.…”
Section: Introductionmentioning
confidence: 99%
“… 40 However, it has been observed that change detection via hyperspectral imaging delivers refined information in various narrow spectral bands that may not be possible with change detection via multispectral imaging. In the previous literature, various change detection techniques were developed and improved to enhance the utilization of hyperspectral imagery, such as convolutional sparse analysis, temporal spectral unmixing, 41 recurrent 3D fully convolutional networks, 42 convolutional long short-term memory, 42 modified U-Net model, 43 principal component analysis, and spectral correlation angle 44 . But the processing of hyperspectral bands with such advanced change detection models may be difficult due to the presence of a large number of spectral bands, which may limit its applicability in various applications.…”
Section: Introductionmentioning
confidence: 99%